2018
DOI: 10.5055/jom.2008.0021
|View full text |Cite
|
Sign up to set email alerts
|

Epidural haloperidol enhances epidural morphine analgesia: Three case reports

Abstract: Epidural

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Although haloperidol has not demonstrated direct effect on pain receptors, its isomeric similarity to meperidine may make it active at opiate receptors . In addition, studies in animals have shown its effect in the NDMA pain modulation pathway, which might also explain its effectiveness for pain control . The analgesic mechanisms attributed to haloperidol might not be clearly elucidated, but randomized clinical trials of intravenous haloperidol have shown safety and effectiveness in treating patients with migraine headache and acute pain in palliative care .…”
Section: Discussionmentioning
confidence: 99%
“…Although haloperidol has not demonstrated direct effect on pain receptors, its isomeric similarity to meperidine may make it active at opiate receptors . In addition, studies in animals have shown its effect in the NDMA pain modulation pathway, which might also explain its effectiveness for pain control . The analgesic mechanisms attributed to haloperidol might not be clearly elucidated, but randomized clinical trials of intravenous haloperidol have shown safety and effectiveness in treating patients with migraine headache and acute pain in palliative care .…”
Section: Discussionmentioning
confidence: 99%
“…Excluded references assessing neuroleptanalgesia for abdominal pain included three case reports,48,49,61 three case series,54,59,84 and one non-randomized controlled trial 61. Ramirez et al34 was excluded as it had a retrospective cohort design.…”
Section: Resultsmentioning
confidence: 99%